INTERFERENSI BAHASA MBOJO DALAM TUTURAN BAHASA INDONESIA SISWA KELAS VII SMPN 4 BOLO, BIMA - Irwansyah Irwansyah (Cendekia: Jurnal Pendidikan dan Pembelajaran, 2017)
This study was initiated by language problems spoken by students of SMPN 4 Bolo, Bima. The study aimed to determine level of interference of native language (Mbojo Language) on Indonesian. This study used descriptive qualitative approach. Subject of this study were students and teachers of SMPN 4 Bolo. Data were collected using observation and interview.  The study discovered that interference of Mbojo language into bahasa Indonesia occurred in:  pronunciation and diction.  pronunciations (sound) in speech included: errors of pronunciation, i.e. changes of phonemes, phoneme disappearance, addition of phonemes, and, pausing pause in a group of words and also interference in sentence level.  Interference on diction appeared in the use of vocabulary, phrase and diction.